Legal Protection For Consumers in Online Buying and Sellin Transactions in Indonesia Reviewed From Law Number 8 Of 1999 Concerning Consumer Protection - Glaidy Angelina Nayoan; Nur Mohamad Kasim; Zamroni Abdussamad (International Journal of Sociology and Law, 2025)
Due to the quick advancement of digital technology, online purchasing and selling has become easier. Online transactions do, however, come with a number of drawbacks, including fraud, mismatches between products and their descriptions, and privacy violations. With reference to Law Number 8 of 1999 on Consumer Protection, the purpose of this study is to examine the legal safeguards that Indonesian consumers have when making purchases online. The study's results, which were obtained using a normative juridical research methodology with an emphasis on statutory regulatory analysis, indicate that while the Consumer Protection Law creates a basic legal framework, more oversight and regulations are necessary to ensure its greater efficacy when applied in the digital sphere.